Psidium guajava (Guava Leaves) Ash and Eggshell Powder as a Alternative for Cement - Bonoy, Diomel Gryle; Directo, Ray Allen; Ordinario, Whynne; Yaco, Reeiz Cussler; Aromin, Krizzalyn Mhae; Morilla, Criscia Maren; Aggalaw, Girly Ann (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study evaluated the effectiveness of Psidium guajava leaf ash (GLA) and eggshell powder (ESP) as partial replacements for cement in mortar mixtures, aiming to develop a more sustainable construction material. Anchored on the pozzolanic reaction theory and the Input-Process-Output framework, the research employed a quantitative experimental design conducted in a controlled laboratory setting. Mortar specimens were prepared using three mixture variations eggshell-dominant, ash-dominant, and equal proportions and were tested using compressive strength measurements, estimated tensile and flexural strength calculations, water absorption tests, and one-way analysis of variance (ANOVA). The findings revealed that the eggshell-dominant mixture achieved the highest compressive strength, ranging from 0.798 MPa to 1.064 MPa, while the other mixtures exhibited no measurable compressive strength. This mixture also demonstrated moderate tensile and flexural performance and acceptable water absorption, indicating balanced mechanical properties and durability. Statistical analysis confirmed significant differences among the mixtures, establishing the eggshell-dominant formulation as the most effective. However, the study identified limitations in the performance of guava leaf ash when used alone or in equal proportions. The results highlight the potential of eggshell powder as a viable partial cement replacement, while further optimization is needed for guava leaf ash. This study aligns with SDG 9 (Industry, Innovation and Infrastructure), SDG 11 (Sustainable Cities and Communities), SDG 12 (Responsible Consumption and Production), and SDG 13 (Climate Action) by promoting sustainable construction materials and waste utilization. The findings contribute to environmental and economic sustainability by reducing reliance on conventional cement, minimizing waste, and supporting cost-effective and eco-friendly construction practices.
Keywords: Cement Replacement; Eggshell Powder; Guava Leaf Ash; Mechanical Properties; Mortar Mixtures; Water Absorption